Homeownership after separation: A longitudinal analysis of Finnish register data - Jalovaara Marika; Kulu Hill (Turku Center for Welfare Research (TCWR), 2022)
BACKGROUND
Divorce and separation have become common life-course events in many European countries. Previous studies show that separated individuals are likely to move from homeownership to renting and experience a period of residential instability. However, little is known about whether and when separated individuals return to homeownership.
OBJECTIVE
This paper investigates homeownership levels after union dissolution in Finland. We extend previous research by examining changes in homeownership levels after separation in the long term and across population subgroups, asking whether and how post-separation homeownership levels are affected by repartnering, by previous homeownership, and by gender.
METHODS
We use Finnish register data and logistic regression analysis.
RESULTS
Compared to partnered individuals, homeownership levels among recently separated individuals are low. With increasing time since union dissolution, homeownership levels increase. However, the levels only increase among repartnered persons, and remain low among non-partnered separated individuals. Low post-separation home-ownership levels partly result from a frequent movement from owner-occupied to rental homes at or soon after separation, but the levels are particularly low among those who also lived in rental homes before separation.
CONTRIBUTION
The study shows short- and long-term effects of separation on individuals’ housing careers. After separation many individuals move from homeownership to rental accommodation, and most previous renters continue to rent. Separated individuals who move in together with or marry a new partner are likely to move/return to homeownership soon after repartnering. In contrast, those who remain non-partnered following separation have a very low likelihood of living in owner-occupied dwellings. This likely reflects constrained opportunities in a country with high homeownership aspirations and levels.